The Development of the Batik Industry in Gemawang Village Semarang Regency (2008–2021) - Jihan Mahetsha Ariyanti; Alamsyah Alamsyah; Siti Maziyah (UIN Sunan Gunung Djati Bandung, 2026)
This article examines the development of the batik industry in Gemawang Village, Jambu District, Semarang Regency, from 2008 to 2021. The study focuses on two key entrepreneurs, Abdul Kholiq Fauzi of CV Batik Gemawang and Saiful Nurudin of Tinctori, who played an important role in revitalising the local batik sector. Their creative work introduced motifs inspired by coffee plants, regional folklore, and Indonesia’s seasonal cycle, particularly the rainy and dry seasons. Using a historical method consisting of heuristic data collection, source criticism, interpretation, and historiography, the research shows that the industry’s growth was influenced by individual initiative, consistency, design innovation, and adaptable marketing strategies. The batik industry contributed to the local economy by creating employment opportunities and fostering community participation. It also supported the development of local tourism through educational visits that showcased traditional batik techniques. Although production and marketing declined during the Covid-19 pandemic, industry actors adapted through online sales and product diversification, allowing gradual recovery. Overall, Gemawang batik industry not only preserves cultural heritage but also strengthens the village’s creative economy.